Considering the Advantages and Disadvantages of Utilizing Social Media to Enhance Learning and Engagement in K-12 Education - Güney, Kaan (Research in Social Sciences and Technology, 2023)
This paper intends to explore the various ways in which social media can be used to enhance learning and engagement, as well as the potential challenges and risks that may arise. The study focuses on face-to-face formal K-12 education which is a system that generally covers 12 grades including primary and secondary schools. The manuscript provides a comprehensive theoretical literature review of the existing research on the topic, highlighting the main findings and discussing the implications. Social media platforms such as Facebook, YouTube, and Twitter have turned into an increasingly prevalent and influential aspect of modern society, and they have also begun to infiltrate the realm of education. However, during this study it has been noticed that there are few studies examining the effects of social media in K-12 education. Namely, some research has been conducted on higher or online education. Accordingly, while there are certainly benefits to applying social media in education, such as the ability to connect with a global network of learners and access to a vast array of information and resources, there are also challenges that must be considered. Thus, the results of this study provide clarification on previous research and lay the foundation for future examinations of the potential advantages and disadvantages of using social media in K-12 education.